Exploring Adult Learners’ Knowledge Construction of Social Foundations Content: One Higher Education Context - Susan Yelich Biniecki; Royce Ann Collins (Adult Education Research Conference, 2017)
This qualitative study explores adult learners’ knowledge construction of social foundations content within a Master of Adult Education program, broadening the understanding of the tenets of constructivist learning.
Keywords: adult learning; higher education; social foundations; constructivist learning